Cr(III) removal and recovery from Saccharomyces cerevisiae - Ferraz, A. I. (2004)
Heavy metal recovery from biosorbents is of major importance in the assessment of competitiveness of biosorption processes. Several desorption agents (H2SO4, HNO3, HCl, CH3COOH and EDTA) were tested for the selection of the optimal elution conditions for Cr(III) recovery from Saccharomyces cerevisiae cells. Sorption time was optimised as it plays an important role in the sorption–desorption process, being shown that a 30 min sorption period is the best option to ensure metal removal from solution and good recovery from biosorbent. The optimal contact time with desorption agents was also studied, as long exposures to these ones may cause cell damage, affecting biosorbent metal uptake capacity in subsequent sorption cycles. Each eluant was analysed in terms of its desorption capacity and its effect on the biomass metal uptake capacity in multiple sorption–desorption cycles. Considering the effectiveness of chromium desorption from loaded biomass, it was possible to conclude that H2SO4 (pH≈1) was the most effective eluant tested, accomplishing the highest Cr(III) recovery from S. cerevisiae in three consecutive sorption/desorption cycles. Regarding the damage caused by acid treatment on S. cerevisiae cells, assessed by the reduction on metal uptake capacity after elution, it was possible to observe that sulphuric acid was the most harmful eluant causing long term negative effects in metal uptake. By the time the experiments were interrupted (nearly 26 h of continuous cycles) biomass uptake capacity was reduced to about 77% of the value reached before acid treatment.